2021
DOI: 10.1017/jfm.2021.563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polydispersity and confinement on diffusion in hydrodynamically interacting colloidal suspensions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Further, our model provides a basis for investigating how protein behavior varies generally with colloidal-scale molecular and cellular properties. For example, confinement (Aponte-Rivera and Zia, 2022; Aponte-Rivera et al, 2018; Gonzalez et al, 2021) (e.g., by a cell membrane) and size polydispersity (Asakura and Oosawa, 1954; Gonzalez et al, 2021; Maheshwari et al, 2022) can induce structural correlations between molecules, which we might expect to augment co-localization driven by UW-PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our model provides a basis for investigating how protein behavior varies generally with colloidal-scale molecular and cellular properties. For example, confinement (Aponte-Rivera and Zia, 2022; Aponte-Rivera et al, 2018; Gonzalez et al, 2021) (e.g., by a cell membrane) and size polydispersity (Asakura and Oosawa, 1954; Gonzalez et al, 2021; Maheshwari et al, 2022) can induce structural correlations between molecules, which we might expect to augment co-localization driven by UW-PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, attractive interactions between the ribosomal L7/L12 domain and ternary complexes (Mustafi and Weisshaar, 2018) or between cognate ternary complexes and mRNA (Grosjean and Chantrenne, 1980) could have the effect of pre-loading or pre-sorting ternary complexes. As a second example, hydrodynamic models of small and large particles confined in a cavity show that both types of particles tend to concentrate near the cavity surface with minor impact on the mobility of small particles (Gonzalez et al, 2021), indicating that ternary complexes and ribosomes may concentrate by the cell membrane (not currently represented in our model) and effectively improve in proximity to each other.…”
Section: Discussionmentioning
confidence: 97%
“…Modeling such forces, in addition to other molecular details like shape, softness, flexibility, and site-specificity, is becoming possible with other algorithms such as Stokesian dynamics for large or confined systems (Aponte-Rivera et al, 2018;Gonzalez et al, 2021;Maheshwari et al, 2019;Ouaknin et al, 2021;Zakhari et al, 2017), but will require substantial integration and iteration with experiments as well as improvements in computational efficiency to achieve accurate simulations over the timescales of cellular behavior (Endy and Brent, 2001). Capturing detailed molecular dynamics, such as those involved with ternary complex-ribosome binding and reactions, will also necessitate multi-scale modeling and experimentation from atomic to cellular scales.…”
Section: Discussionmentioning
confidence: 99%
“…Computational studies showed similar effects influencing the self-diffusion close to interfaces. 4 However, the existing explicit comparisons between experiment and colloid theory do not sufficiently address the genuine effects of polydispersity, for example, the experimental results in ref ( 39 ) can still be approximately described by an effective monodisperse system due to the experimental restriction to only one type of tracer protein.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the diffusive transport of macromolecules in the polydisperse and crowded ensemble within the aqueous intracellular fluid of living cells is crucial to understand their function. , Polydispersity and crowding are, thus, subject to numerous theoretical, simulation, ,, and experimental studies. Both living cells or even small organisms in their entire complexity and settings with different degrees of simplification have been explored using spectroscopic methods, such as nuclear magnetic resonance (NMR), , Mössbauer spectroscopy, and fluorescence correlation spectroscopy. Drastically simplified model systems with well-defined and adjustable configuration parameters can help to test models, many of which are derived from colloid physics. …”
Section: Introductionmentioning
confidence: 99%